Case Report: Inguinal Myxofibrosarcoma Arising From the Surgical Site of Resected Squamous Cell Carcinoma - Hu, Hongyu; Hu, Xianwen; Li, Dandan; Cai, Jiong; Wang, Pan (Frontiers in Oncology, 2022)
Myxofibrosarcoma (MFS) is a rare soft tissue sarcoma that originates in the mesenchymal tissue and occurs mainly in the limbs of elderly patients. Herein, we present the case of a 64-year-old woman who underwent extensive left vulvar resection and bilateral lymphadenectomy for vulvar squamous cell carcinoma 6 months previously. A mass was found again at the original surgical site of the left groin three months prior, and it had increased significantly in the past 1 month, with ulceration and pus. Magnetic resonance imaging (MRI) showed a 10-cm mass in the left groin area; fluoro18-labeled deoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) showed a marked increase in mass metabolism in the left groin area, which was highly suspected to be a recurrence of squamous cell carcinoma. Subsequently, the patient underwent surgery and the postoperative pathology and immunohistochemistry confirmed myxofibrosarcoma. In conclusion, myxofibrosarcoma has rarely been reported to arise from the surgical site of squamous cell carcinoma. Our case study demonstrates that myxofibrosarcoma should be included in the differential diagnosis of superficial masses in patients with a prior surgical history who present with a soft tissue mass at the surgical site, especially for recently developed rapidly increasing masses. This study aimed to systematically review the clinical features, diagnosis, differential diagnosis, treatment, and prognosis of this disease based on our case and related published literature and to provide clinicians with a broader perspective on the differential diagnosis of soft tissue tumors.